AKULTURASI BUDAYA KUBUR TEMPAYAN DAN MEGALITIK: STUDI KASUS SITUS MUARA BETUNG, SUMSEL - Sugiyanto, Bambang (Berkala Arkeologi, 2002)
Megalithic culture that spreads in Indonesia, has a unit of time (chronology) of development between 2500 BC - the first centuries AD. Several megalithic sites found in Sumatra, Java, Sulawesi, Ambon, Nusa Tenggara and Papua, almost all tend to show independent megalithic culture. Only certain sites show other cultural characteristics, such as: Gilimanuk, which shows a different burial culture between megalithic graves, jar burials and burials without containers (direct). Then the Lambanapu site in Nusa Tenggara also shows mixed burials between jars and burials without a container. In general, in the megalithic tradition there is one freedom in choosing a burial container to use. This can be seen from the various types and forms of megalithic burials found, ranging from menhirs, stone cists, waruga, kalamba, stone circles, and dolmen. In principle, all the burial containers can be used according to their wishes and abilities, which are also adjusted to the availability of raw materials in their environment.